Stratified Oil-Water Two-Phases Flow of Subsea Pipeline - Alias, Adib Zulhilmi Mohd; Ahmed, Yasser Mohamed; Junaidi, Abd Khair; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Oil-water two-phase flow in 0.0254m horizontal pipe is simulated using FLUENT 6.2. The stratified flow regime is modeled using Volume of Fluid (VOF) with turbulent model RNG k-?. Grid independent study has been conducted to decide mesh size for solution accuracy and optimum computational cost. The simulation is performed in time-dependent simulation where oil and water are initially separated by patching the region base on difference in density. Observation on the effect of velocity to the pressure gradient was also simulated. Flow velocity at 0.2, 0.5, 0.8 and 1.1 m/s with same volume fraction for each phase with appropriate multiphase model and turbulence model are presented.